Prevalencija intrahospitalnih infekcija u istočnoj Hercegovini - Slavenka Janković; Biljana Mijović; Janja Bojanić; Nina Rodić Vukmir (Биомедицинска истраживања, 2013)
Introduction: . Hospital-acquired infections (HAIs) are a global public health problem. Surveillance has been widely accepted as the primary tool in the control of HAI. It assumes systematic collection, analysis and interpretation of HAI data, as well as providing feedback information for personnel in health care settings. Prevalence study is a fast, simple and relatively inexpensive surveillance method. The aim of this study was to assess the magnitude of the problem of HAIs in hospitals of East Herzegovina in the Republic of Srpska. Methods: . At the time of conducting this study (August 2011) there were 483 patients hospitalized, out of whom 234 were involved in this study. Patients who spent at least 72 hours in hospital were included in the study. According to the CDC (Centers for Disease Control and Prevention) definition only clinically manifested HAIs were considered. Results: . The prevalence of patients with HAIs was 4.2%, which is exactly the same value as the HAI prevalence. The highest prevalence of patients with HAI was registered at the Department of Neurology (15.7%), followed by the Surgical Intensive Care Department (12.5%) and Gynecology Department (12.5%), while the least prevalence was found at the Department of Surgery (6.2%). The highest prevalence was registered in the group aged between 40 and 59 years. The causative agents of HAI were isolated in 40% of cases. By anatomic localization, the most common were infections of the surgical site (40%) and diges tive system (40%), followed by urinary tract infections (10%) and skin and soft tissue infections (10%). Conclusion: . The results of this study showed that the prevalence of HAI is within the frame of the prev alence in developed countries. However, their occurrence in patients with low risk for HAI indicates that more attention must be given to this problem. The prevalence study can be a tool of routine HAI surveillance at a national level.
Keywords: prevalence study; hospital-acquired infections; the Republic of Srpska